2021
DOI: 10.1136/bmjopen-2020-047202
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of exacerbation frequency of AECOPD based on next-generation sequencing and its relationship with imbalance of lung and gut microbiota: a protocol of a prospective cohort study

Abstract: IntroductionPatients with frequent acute exacerbation phenotype chronic obstructive pulmonary disease (AECOPD) have a higher hospitalisation rate than infrequent exacerbation, the disease progresses quickly and treatment is more difficult. At present, it is impossible to predict patients with COPD with frequent acute exacerbation phenotypes. The composition of the lower respiratory tract flora and the intestinal flora is closely related to AECOPD, but the specific association mechanism between them is not very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Studies have shown associations between gut dysbiosis and changes in lung microbiota composition, as well as the impact of lung microbiota disruptions on gut health [ 10 ]. In the stool of patients with stable COPD, the level of beneficial bacteria significantly decreased, such as bifidobacteria and lactobacilli [ 11 ]. Analysis of gut microbiota in COPD patients with different GOLD grades also revealed some correlations between severity and microbiota pattern: in COPD with GOLD 1, the abundance of Bacteroides was higher, and the abundances of Tyzzerella 4 and Microbacterium spp.…”
Section: The Cause-and-effect Of Intestinal Microecology On Copdmentioning
confidence: 99%
“…Studies have shown associations between gut dysbiosis and changes in lung microbiota composition, as well as the impact of lung microbiota disruptions on gut health [ 10 ]. In the stool of patients with stable COPD, the level of beneficial bacteria significantly decreased, such as bifidobacteria and lactobacilli [ 11 ]. Analysis of gut microbiota in COPD patients with different GOLD grades also revealed some correlations between severity and microbiota pattern: in COPD with GOLD 1, the abundance of Bacteroides was higher, and the abundances of Tyzzerella 4 and Microbacterium spp.…”
Section: The Cause-and-effect Of Intestinal Microecology On Copdmentioning
confidence: 99%
“…In the management of COPD, some researchers have argued that remote monitoring may be a promising alternative or an adjunct to traditional health care services [ 22 ]. In recent years, many studies have established risk factors prediction models for acute exacerbation in COPD patients through different monitoring methods, including electronic medical records [ 23 ], questionnaire diary records [ 24 ], or telephone follow-up [ 25 ]. Nonetheless, it is not always possible to monitor all exacerbations in terms of frequency, severity, and likely causes.…”
Section: Introductionmentioning
confidence: 99%
“…6 In the patients with acute exacerbation phenotype chronic obstructive pulmonary disease, mNGS was employed to explore the lung and gut microbiota, and it is expected that the clarified intestinal microenvironment of patients will benefit the drug development. 7 Advances in transcriptome sequencing technology (RNAseq) are broadening our vision of host responses to Mtb infection. Cai et al performed single-cell transcriptomics of blood and proved a depletion of natural killer cell subset in TB patients, which could be relieved after anti-TB treatment.…”
mentioning
confidence: 99%
“…A study performing mNGS for 92 acute respiratory failure patients revealed the pathogens and the airway microbiome, thereby identifying patients with lower respiratory tract infections . In the patients with acute exacerbation phenotype chronic obstructive pulmonary disease, mNGS was employed to explore the lung and gut microbiota, and it is expected that the clarified intestinal microenvironment of patients will benefit the drug development …”
mentioning
confidence: 99%